Anti-Salmonella and Antibiofilm Potency of Salvia officinalis L. Essential Oil against Antibiotic-Resistant Salmonella enterica - Samy Selim; Mohammed S. Almuhayawi; Hussain Alqhtani; Soad K. Al Jaouni; Fayez M. Saleh; Mona Warrad; Nashwa Hagagy (MDPI AG, 2022)
Raw milk is a significant vehicle for the transmission of different infections. In the present study, we focused on Salmonella enterica from raw milk and its resistance to various antibacterial drugs. Furthermore, we have investigated the antimicrobial and antibiofilm effects of essential oil (EO) obtained from Salvia officinalis L. leaves that were collected from the Aljouf region, Saudi Arabia, against S. enterica. One-dozen strains of S. enterica were found in a batch of a hundred milk samples, and those S. enterica strains were shown to be resistant to several antibiotics, particularly the β-lactam group of antimicrobial drugs. Against multidrug-resistant S. enterica, the inhibitory zones for EO from S. officinalis leaves were found to be 21 mm in diameter. S. officinalis EO at 5% concentration showed a remarkable in vitro inhibitory activity toward the biofilm growth of different S. enterica isolates. Analysis of EO by GC-MS identified 21 distinct components, accounting for 89.94% of the total oil component. The most prominent compounds were 1,8-cineole (39.18%), β-caryophyllene (12.8%), and α--terpineol (10.3%). Taken together, our results unequivocally confirm that the S. officinalis EOs exert numerous bioactivities. Thus, the well-deserved attention on S. officinalis EO usage as a food preservative and adjunctive remedy for bacterial food-borne diseases is justified.